PENGGUNAAN BEBERAPA EKSTRAK TUMBUHAN SEBAGAI INSEKTISIDA NABATI UNTUK PENGENDALIAN HAMA DAUN KUBIS (Plutella xylostella L.) DI KABUPATEN DONGGALA - Nurkhasanah Nurkhasanah (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
Diamondback moth P. xylostella attack on cabbage crop represents one of the main constraints in the crop development in Donggala regency Central Sulawesi.  Plant extracts as insecticide to control the pest can be developed to overcome the constraint. The research aimed at determining the effectiveness of various plant extracts to suppress P.xylostella . The research was conducted in       a central plantation of cabbage in Nupa Bomba, Tawaeli sub district or Donggala regency, from March to October 2008.  This research used a Randomized Block Design with 5 treatments: K0 = Control (water), K1 = Widuri extract, K2 = Srikaya extract, K3 = Dringo extract and K4 = matador 25 EC insecticide. Each treatment was repeated 4 times giving 20 experimental units. The experimental  parameter observed were (i) density of larva population, and (ii) crop weight per plot. Data were analysis using analysis of variance, whether the treatments were significant, advanced analysis of Duncan Multiple Range Test at 5% significant level was used.  The research results showed that the various plant extracts have significant effect on population density of the larva diamondback moth (P.xylostella) and the cabbage weight.  The largest number of dead larvae  was found in K3 treatment K3 (extract of Dringo leaf).  In the same treatment, the cabbage weight per crop was also higher than any other treatment.